2002
DOI: 10.1116/1.1502702
|View full text |Cite
|
Sign up to set email alerts
|

Copper sample analyzed with an n-doped silicon tip using conducting probe atomic force microscopy

Abstract: Articles you may be interested inElectrical transport and mechanical properties of alkylsilane self-assembled monolayers on silicon surfaces probed by atomic force microscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A potential complication in measurements of impedance and current as a function of applied bias can occur in AFMs with laser-based feedback due to photoexcitation of carriers in the probe and/or the sample. This effect has been observed in both silicon (Buh and Kopanski, 2003) and copper samples (Schneegans et al, 2002), where it was mentioned that the magnitude varies with both the position and intensity of the laser. Buh and Kopanski (2003) also reported that carrier lifetimes can be measured from the transient behavior induced by turning off the laser.…”
Section: Ac C-afm Techniquesmentioning
confidence: 81%
“…A potential complication in measurements of impedance and current as a function of applied bias can occur in AFMs with laser-based feedback due to photoexcitation of carriers in the probe and/or the sample. This effect has been observed in both silicon (Buh and Kopanski, 2003) and copper samples (Schneegans et al, 2002), where it was mentioned that the magnitude varies with both the position and intensity of the laser. Buh and Kopanski (2003) also reported that carrier lifetimes can be measured from the transient behavior induced by turning off the laser.…”
Section: Ac C-afm Techniquesmentioning
confidence: 81%